2008
DOI: 10.1007/s12010-008-8288-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antagonistic Metabolites of Established Biocontrol Agent of Marine Origin

Abstract: Biocontrol ability of Pseudomonas aeruginosa ID 4365, a biocontrol agent of groundnut phytopathogens from marine origin, was previously attributed to the production of pyoverdin type of siderophores. However, pyoverdin-rich supernatants of this organism showed better antifungal activity compared to equivalent amount of purified pyoverdin indicating presence of undetected metabolite(s) in pyoverdin rich supernatants. On the basis of observation that antagonistic activity was iron-dependent and iron-independent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 26 publications
(24 reference statements)
1
5
0
2
Order By: Relevance
“…Further purification was performed according to the method of Rane et al . (). HPLC‐MS analysis showed that the pyocyanin component did not contain other metabolites.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Further purification was performed according to the method of Rane et al . (). HPLC‐MS analysis showed that the pyocyanin component did not contain other metabolites.…”
Section: Methodsmentioning
confidence: 97%
“…The fermentation broth was then centrifuged to remove the cell mass, and the supernatant was extracted with an equal volume of chloroform. Further purification was performed according to the method of Rane et al (2008). HPLC-MS analysis showed that the pyocyanin component did not contain other metabolites.…”
Section: Preparation Of Pyocyaninmentioning
confidence: 99%
“…It has been reported that a lower concentrations of pyocyanin act as inhibitors (Hassanein et al, 2009). Rane et al (2008) also reported the biocontrol activity of pyocyanin against C. falcatum, F. oxysporum, and Sclerotium rolfsii. In conclusion, although encouraging results were achieved from using phenazines to control G. boninense in vitro, studies must be done to confirm their efficacy in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Lahkar et al (2015) revealed the ability of the strain JS29 to inhibit the growth of Alternaria solani, the causal agent of tomato blight, by 73%. Meanwhile, P. aeruginosa ID 4365 and SBC 5 were demonstrated to have good antifungal ability against Sclerotium rolfsii, the causal agent of Southern blight on vegetables and melons (Rane et al, 2008).…”
Section: Phylogenetic Analysismentioning
confidence: 99%